APLIKASI SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT AYAM BERBASIS WEBSITE MENGGUNAKAN METODE CERTAINTY FACTOR - Ery Murniyasih; Pujianti Wahyuningsih (Electro Luceat, 2021)
Disease in chicken can be caused by bacteria, viruses, fungi, parasites from within or from outside. This condition will cause the level of chicken production to decrease if exposed to chicken disease. The purpose of this study was to design and implement an expert system for early diagnosis in web-based chicken using the certainty factor method. Certainty factor method in this study aims to provide certainty for the user to know where the chicken that detected a disease. Certainty provided by these experts describe the beliefs of an expert in the relationship between antecedent and consequent. The results of this study are to produce a web-based application system that can diagnose diseases in chicken so that users can find out what diseases are experienced by chicken by inputting the symptoms that appear. This study focuses on the type of broiler chicken with the type of Gumboro disease, Newcastle disease, respiratory disease, bird flu, and defecation lime